The association between the risk of relative energy deficiency in sports and performance outcomes: A real-world examination of international elite volleyball male athletes - Sesbreno, E.; Dziedzic, C.; Blondin, D. P.; Kennedy, C.; Sygo, J.; Haman, F.; Deslauriers, J.; Brazeau, A.-S.; Mountjoy, M. (Journal of Sports Sciences, 2025)
Background Relative Energy Deficiency in Sports (REDs) has been reported in Olympic-level male athletes, but the impacts of REDs on performance is unclear. This study explored the association between international elite level volleyball male athletes at risk of REDs and countermovement jump (CMJ) and cognitive performance in real-world setting.